Upaya Meningkatkan Intensitas Berahi Pada Kerbau Dalam Hubungannya Dengan Peningkatan Angka Konsepsi Hasil Inseminasi Buatan - Tongku N Siregar (Fakultas Peternakan Universitas Jambi, 2008)
This experiment was conducted to determine the corelation between estrous intensity and increasing conception rate which is resulted from artificial insemination at local buffalo. For that purpose, 15 local female buffaloes belong to farmer in Lampu’uk Kuta Baro Aceh Besar, were used. The buffaloes were divided into two groups randomly, which consist of five buffaloes for control and ten bufflaoes for treatment groups. The first group were not given any treatment and performed the estrus naturally, while the second group were synchronized the estrous time with CIDR-B. Insemination in control group were carried out base on request from the farmer to the inseminator, whereas in treatment group, the insemination were done 24 hours post removing of CIDR-B. The measurement of estrous intensity were done during insemination time using scoring method developed by Eerdenburg et al (1996). The pregnancy detection were done on the inseminated buffaloes 21 days post IB through no return estrous observation and rectal palapation 90 days post IB. The result showed that there were significant increasing of estrous intensity in treatment group (15.80+5.02) compared to control group (2.60+4.34). The correlation between estrus intensity and pregnancy percentage showed the significant correlation (r=0.553).